Default Risk on Islamic Banking in Indonesia - Misnen Ardiansyah; Aris Munandar; Ahmad Syahrul Fauzi; Ulufun Naimah (Global Review of Islamic Economics and Business, 2014)
Stability of financial institutions is a crucial issue amid the economic crisis that hit the US and Europe. Islamic banking in Indonesia as financial institutions are also required to have good stability in order to maintain the stability of the national economy. The aim of this research is to determine the stability of Islamic banking in Indonesia, and understand the factors that affect the stability. Stability of Islamic banking will be measured using Merton model  to estimate the Probability Default (PD). Panel data regression was used to estimate the factors that affect the stability of Islamic Banking. The object of this research is 10 Islamic banking in Indonesia that meet the specified criteria. From the analysis of the Merton model, the research found that the stability of Islamic banking in Indonesia is not good enough. This can be seen from the value of the probability default on Islamic banking which still above 0.5. However, based on the trend, the probability default of Islamic banking has decreased from year to year. Some of the variables that influence the stability of Islamic banking is asset and BI rate (SBI).